solve this question this is hard question
Attachments:
![](https://hi-static.z-dn.net/files/d74/5b0707d72b0a74dfdee777d518bc7bdd.jpg)
Answers
Answered by
2
Answer:
98
Step-by-step explanation:
Take the following as examples:
(2*3)+(2*(2-1))=8
(4*5)+(4*(4-1))=27
Therefore, going with that logic:
(7*8)+(7*6)=98
Thank you!
Answered by
2
here 2+3=8
first we multiply 2×3=6
then we take 2 - 1 = 1
now 2×1=2
6+2=8
now 7+8=??
7×8=56
7 - 1 = 6
6×7=42
42+56=98
hence,answer is 98
this is my answer
please brainliest me please brainliest
Similar questions